Pengaruh Current Ratio, Net Profit Margin, dan Debt To Equity Ratio terhadap Earning Per Share pada Perusahaan Farmasi yang Terdaftar di Bursa Efek Indonesia Tahun 2014-2020 - Kumba Digdowiseiso; Agustina Agustina (Syntax Corporation, 2022)
This study aims to analyze the effect of Current Ratio, Net Profit Margin, and Debt to Equity Ratio on Earning Per Share in Pharmaceutical Companies. The source of this research data uses secondary data, namely in the form of financial reports on the www.idx.co.id site. The financial reports observed are the financial statements of pharmaceutical companies for 2014-2020. The data of this study were analyzed on 10 pharmaceutical companies listed on the Indonesia Stock Exchange. In taking the sample for this study using purposive sampling method. The data analysis technique used is linear regression analysis and hypothesis testing using a T test that has been processed in STATA 16 to test the regression coefficients. Based on the results of the study, it was found that the Current Ratio had a negative and insignificant effect on Earning Per Share, Net Profit Margin had a positive and significant effect on Earning Per Share, and the Debt to Equity Ratio had a positive and significant effect on Earning Per Share